2015
DOI: 10.1002/jts.22056
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic Distress Mediates the Effect of Severity of Disaster Exposure on Perinatal Depression: The Iowa Flood Study

Abstract: Disaster exposure during pregnancy has received limited attention. This study examined the impact of the 2008 Iowa Floods on perinatal maternal depression and well-being, and the role of peritraumatic distress as a possible mechanism explaining this link. Perinatal women (N = 171) completed measures of depressive symptoms and general well-being at 5 timepoints from pregnancy to 30 months postpartum. Objectively assessed prenatal flood exposure was associated with greater depression (r = .15). Further, flood-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 38 publications
(47 reference statements)
1
24
1
Order By: Relevance
“…Objective hardship was estimated using the Queensland Flood Objective Stress Scale (QFOSS; King et al., ), based on previous disaster research (Brock et al., ; Yong Ping et al., ) and tailored to the unique circumstances of the Queensland floods to maximize sensitivity. QFOSS assessed four dimensions of flood‐related hardship: (1) threat (e.g., “Were you injured?”), (2) loss (e.g., “Did you experience loss of personal income?”), (3) scope (e.g., “How many days were you without electricity?”), and (4) change (e.g., “Did you spend any time in a temporary shelter?”).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Objective hardship was estimated using the Queensland Flood Objective Stress Scale (QFOSS; King et al., ), based on previous disaster research (Brock et al., ; Yong Ping et al., ) and tailored to the unique circumstances of the Queensland floods to maximize sensitivity. QFOSS assessed four dimensions of flood‐related hardship: (1) threat (e.g., “Were you injured?”), (2) loss (e.g., “Did you experience loss of personal income?”), (3) scope (e.g., “How many days were you without electricity?”), and (4) change (e.g., “Did you spend any time in a temporary shelter?”).…”
Section: Methodsmentioning
confidence: 99%
“…Mothers completed the short‐form Depression Anxiety and Stress Scales (DASS‐21; Lovibond & Lovibond, ) at 16 months, endorsing the degree to which they experienced a range of symptoms using a 4‐point scale, yielding depression, anxiety, and stress subscales. Only the depression subscale was used in the present study, based on previous evidence of an increased risk of depression following exposure to a natural disaster (Brock et al., ; Fergusson, Horwood, Boden, & Mulder, ; Qu et al., ), an association between maternal depression and child behavior (Barker, Jaffee, Uher, & Maughan, ; Feldman et al., ), and to control for the influence of maternal mood on reports of child behavior (Najman et al., ). Cutoff scores for normal (0–9), mild (10–13), moderate (14–20), severe (21–27), and extremely severe (28+) levels of depressive symptoms are provided in the manual (Lovibond & Lovibond, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that pregnant women had higher depressive symptoms and a lower sense of well‐being for 2.5 years after the flood (Brock et al. ). Another study found that children born to women who were pregnant during the flood had increased risk of obesity (Dancause et al.…”
Section: Intergenerational Stress Resilience and Recovery: The Bodymentioning
confidence: 99%
“…Pregnant women who have experienced disasters are at greater risk of antenatal depression and adverse birth outcomes (Harville et al, 2009;Xiong et al, 2010;Brock et al, 2015). Moreover, maternal depression and stress may augment unhealthy behaviours, such as smoking and drinking alcohol during pregnancy, and may interfere with optimal nutrition (Harville et al, 2010).…”
Section: Reproductive Healthmentioning
confidence: 99%